VERAPAMIL USE IN CHRONIC HYPERTENSION PREGNANT WOMEN : A SYSTEMATIC REVIEW - Dhillon, Robinder; Auliya, Ahsan; Azhari, Ririn (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Verapamil is a medication that has been approved for the treatment of high blood pressure, abnormal heart rhythm, or angina (chest discomfort or shortness of breath). Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 115 articles, whereas the results of our search on SagePub brought up 21 articles. The results of the search conducted for the last year of 2013 yielded a total 11 articles for PubMed and 8 articles for SagePub. In the end, we compiled a total of  5 papers, 3 of which came from PubMed and 2 of which came from SagePub. We included five research that met the criteria. Conclusion: Verapamil can be taken during pregnancy, although it is not commonly used. If patients need to take verapamil to treat high blood pressure, usually will be switched to different medicine. There are limited study and research about verapamil and its use to treat chronic hypertension in pregnancy woman.